Factors of local recurrence rate after whole breast irradiation with and without boost radiotherapy after conserving surgery - Nagykálnai, Thomas (Radiology and oncology (Ljubljana), 1997)
The authors analysed and evaluated 111 records of patients after breast conserving surgery (BCS) followed by radiotherapy. They found 6 factors that could be examined on a routine basis, which were grouped as "high" and "medium" risk factors. The authors consider the boost technique necessary in the presence of 1 "high" or 2 "medium" risk factors.
Keywords: Breast neoplasms; Neoplasm recurrence, local; Radiotherapy; Surgery